Long-term survival of retained cementless hip stems at an average of 13 years after isolated cup revision - Innmann, Moritz Maximilian; Peitgen, David S.; Merle, Christian; Bruckner, Thomas; Gotterbarm, Tobias; Moradi, Babak; Streit, Marcus R. (The journal of bone & joint surgery. A, American volume, 2019)
Background: Cementless stems demonstrate excellent long-term survival, but little is known about the long-term survival rate of the stem after isolated cup revision. The aim of the present retrospective cohort study was to determine the long-term survival rate of cementless stems retained after prior cup revision. Methods: We reviewed the clinical and radiographic results of 119 total hip arthroplasties (THAs) utilizing a cementless, grit-blasted, tapered titanium femoral stem that were performed in 113 patients between January 1985 and December 1989. The mean age at the time of the primary THA was 52 years (range, 16 to 74 years) and the mean time between primary THA and cup revision was 13 years (standard deviation [SD], 6 years; range, 0 to 30 years). At the time of the latest follow-up, no patient was lost to follow-up, 36 patients representing 37 hips had died, and 11 hips in 11 patients had required stem revision. The mean follow-up was 13 years following cup revision (SD, 6 years; range, 0 to 28 years). A competing risk analysis was performed to estimate the survival of the stem after isolated cup revision, with death being the competing risk factor. Results: At 20 years after cup revision, the survival rate of retained stems was 89% (95% confidence interval [CI], 79% to 94%) for the end point of stem revision for any reason and 97% (95% CI, 91% to 99%) for the end point of stem revision for aseptic loosening. Conclusions: The long-term survival of cementless stems retained after cup revision was excellent. Well-fixed cementless stems should be retained during cup revision for aseptic loosening. Level of Evidence: Level IV. See Instructions for Authors for a complete description of levels of evidence.
Gesehen am 16.08.2019